2020
DOI: 10.1371/journal.pone.0241065
|View full text |Cite|
|
Sign up to set email alerts
|

Cost comparison of nine-month treatment regimens with 20-month standardized care for the treatment of rifampicin-resistant/multi-drug resistant tuberculosis in Nigeria

Abstract: Background Globally, drug resistant tuberculosis (DR-TB) continues to be a public health threat. Nigeria, which accounts for a significant proportion of the global burden of rifampicin/multi-drug resistant-TB (RR/MDR-TB) had a funding gap of $168 million dollars for TB treatment in 2018. Since 2010, Nigeria has utilized five different models of care for RR/MDR-TB (Models A-E); Models A, B and C based on a standardized WHO-approved treatment regimen of 20–24 months, were phased out between 2015 and 2019 and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
(51 reference statements)
2
8
0
Order By: Relevance
“…Three studies, from Ethiopia, Nigeria and South Africa, noted that treatment costs per patient was lower by 24.9%, 48.8% and 54.6% in the three countries, respectively, when ambulatory care was compared to hospital-based care (Table 4). 34,37,39 The same was noted by two studies comparing treatment costs between hospital-based and community-based approaches. These studies noted that 77.7% and 49.1% less cost was incurred when treatment was offered using community-based models than using centralized models in South Africa and Nigeria, respectively (Table 4).…”
Section: Cost Of Mdr-tb Caresupporting
confidence: 56%
See 1 more Smart Citation
“…Three studies, from Ethiopia, Nigeria and South Africa, noted that treatment costs per patient was lower by 24.9%, 48.8% and 54.6% in the three countries, respectively, when ambulatory care was compared to hospital-based care (Table 4). 34,37,39 The same was noted by two studies comparing treatment costs between hospital-based and community-based approaches. These studies noted that 77.7% and 49.1% less cost was incurred when treatment was offered using community-based models than using centralized models in South Africa and Nigeria, respectively (Table 4).…”
Section: Cost Of Mdr-tb Caresupporting
confidence: 56%
“…Twelve studies were eligible and included in this review (Figure 1). Five studies were from the southern African region (South Africa), 11,[33][34][35][36] two from the west African region (Nigeria) 37,38 and ve from the east African region (Ethiopia (n=2), 39,40 Tanzania (n=1), 41 Uganda (n=1) 42 and Kenya (n=1) 43 ). Four of the included studies were cohort studies, 11,33,36,41 5 were cost analyses, 34,35,[37][38][39] 2 were interrupted time series 40,42 and one was a cross sectional study 43 (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…TB regimen costs have been studied before, but previous assessments have calculated regimen costs without considering drug import costs [42][43][44][45][46][47][48]. This study extends previous assessments of DS-TB and MDR-TB regimen costs by estimating the costs of drug regimens including regimen-specific import costs.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast to our bottom-up analysis of TB regimen import costs, the cost-effectiveness analysis derived a common import cost estimate for all imports based on trade-flow data for the entire country [30]. The costs of DS-TB and MDR-TB regimens without import costs, in turn, have been frequently calculated before, either as stand-alone cost analyses [42][43][44] or within cost and cost-effectiveness analyses of TB programs [45][46][47][48]. In a systematic review of DS-TB and MDR-TB treatment costs from 2015, a standard 6-month DS-TB regimen had a mean cost of $39 in lower-middle income countries, which is the World Bank income group to which Uzbekistan belongs to; a conventional longer regimen for MDR-TB had a mean cost of $2930 [47].…”
Section: Comparison With Previous Findingsmentioning
confidence: 99%
“…In studies of TB programs in Peru, Estonia, Russia, and the Philippines, TB drugs contributed 35%, 19%, 26%, and 46%, respectively, to the costs of a conventional MDR-TB treatment course [14][15][16]. In another study of a TB program in Nigeria, drugs contributed 6.5-12.6% to the costs of a conventional MDR-TB treatment course, 8.8-15.6% to the costs of a 9-12months MDR-TB treatment course with an injectable agent, and 25.8% to the costs of an 9-12-months all-oral MDR-TB treatment course [17]. For 6-months DS-TB treatment, a systematic review found that the purchase of TB drugs can contribute 14.2% to the TB treatment costs in lower-middle-income countries and 19% in low-income countries [18].…”
mentioning
confidence: 99%